Scientific statement on the health‐based guidance values for dioxins and dioxin‐like PCBs - European Food Safety Authority (EFSA Journal, 2015)
Abstract Different organisations have undertaken risk assessments of dioxins resulting in the issuance of a range of health‐based guidance values. This report examines the approaches taken by the Scientific Committee on Food (SCF), the Joint FAO/WHO Expert Committee on Food Additives (JECFA) and the United States Environmental Protection Agency (US EPA) and how these differing approaches impact on the final derivation of a numerical value. SCF and JECFA concluded that the critical studies for derivation of a health‐based guidance value (HBGV) were animal studies, whereas the US EPA selected the human data, as their preference is to use human data where available. SCF and JECFA applied a body burden one‐compartment kinetics approach to derive a HBGV from rat data, whereas US EPA applied physiologically based pharmacokinetic modelling of blood levels estimated from epidemiology studies. An uncertainty factor of 3 was applied by SCF and JECFA as the lowest‐observed‐adverse‐effect level (LOAEL) was close to the no‐observed‐adverse‐effect level (NOAEL) (observed in another animal study), as opposed to the US EPA applying their default uncertainty factor of 10 for extrapolation from a LOAEL in the absence of a NOAEL. This resulted in the reference dose set by US EPA being 3‐fold lower than the tolerable weekly intake (TWI)/provisional tolerable monthly intake (PMTI). In view of the different approaches used in the most recent assessments undertaken by the authorities, it would appear appropriate to undertake a comprehensive risk assessment on the risks for animal and human health related to the presence of dioxins and dioxin‐like polychlorinated biphenyls (dl‐PCBs) in feed and food.